2019
DOI: 10.1109/toh.2018.2879812
|View full text |Cite
|
Sign up to set email alerts
|

Toward Whole-Hand Kinesthetic Feedback: A Survey of Force Feedback Gloves

Abstract: Force feedback gloves have found many applications in fields such as teleoperation and virtual reality. In order to enhance the immersive feeling of interaction with remote or virtual environments, glove-like haptic devices are used, which enable users to touch and manipulate virtual objects in a more intuitive and direct way via the dexterous manipulation and sensitive perception capabilities of human hands. In this survey, we aim to identify the gaps between existing force feedback gloves and the desired one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 105 publications
0
53
0
Order By: Relevance
“…Based on actuation type, we can classify them into electrical motors, pneumatic or hydraulic actuators, novel actuators using functional materials etc. Readers may refer to existing survey about force feedback gloves [49] or wearable haptic devices [50] .…”
Section: Wearable Haptic Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Based on actuation type, we can classify them into electrical motors, pneumatic or hydraulic actuators, novel actuators using functional materials etc. Readers may refer to existing survey about force feedback gloves [49] or wearable haptic devices [50] .…”
Section: Wearable Haptic Devicementioning
confidence: 99%
“…In order to provide more realistic haptic sensations, more research prototypes of force feedback gloves have been developed [49,50] . Figure 27a shows a lightweight glove using pneumatic-driven rigid actuators and an underactuated mechanism with a single transmission link, which effectively reduces the weight of the glove while maintaining the sufficient workspace [62] .…”
Section: Wearable Haptic Devicementioning
confidence: 99%
“…It has been designed for applications in virtual and augmented reality. A review of the literature on lightweight exoskeletons for the hand can be found in [1], [12]. Indeed, providing both cutaneous and kinesthetic feedback has often showed better performance than providing either cutaneous or kinesthetic feedback alone.…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach in evolving from grounded haptic interfaces to more wearable and portable designs has been to move the grounded part of the haptic interface from an external support onto the body of the human user. Such body-grounded haptic interfaces have been called exoskeletons and they have been very successful in the past [2], [14]. However, although exoskeletons do show an increased wearability and portability with respect to grounded solutions, they have one significant limitation.…”
mentioning
confidence: 99%
“…Wearable and hand-held haptic devices are increasingly present in teleoperation, gaming, rehabilitation, VR, AR, and many other application domains [1], [2]. This growing popularity is supported by an increasing number of research and studies aimed to define methods, principles, and guidelines for the design of wearable and hand-held interfaces [1], [2], [4]- [6]. However, the definition of what is a wearable or hand-held device is not always as intuitive and straightforward as it may seem.…”
mentioning
confidence: 99%